Confessional text in the light of Yuri Lotman's semiotic research. - Hajdu, Péter; Lutsewich, Lyudmila (Neohelicon, 2022)
Yuri Lotman developed and during his career frequently revisited the concept of "culture as text," which he demonstrated to be universal. Within the framework of the semiotic approach, culture, perceived as a text, is, according to Lotman, a complexly encoded structure. This article attempts to consider confessional texts in the light of Lotman's semiotic model of culture. Following his methodology, we assume that confessional discourse in natural language historically preceded the speech genre 'confession'; early Christianity developed confession as a 'ritualized formula', after which the 'ritual' was transformed into a literary and artistic semiotic model. Literary confession invariably retains the characteristic method of semiotically encoded information throughout its long existence. Moreover, being included in new textual and extra-textual contexts, the confessional text creates new meanings that enrich, complicate, and change its semantics. Adapted to different contexts, confession acquires new functions and new recoding options. Drawing on Lotman, it is possible to see the analogy between the text and the symbolic behavior of the personality, as well as the actualization of the addresser and the addressee in the process of communication both with 'self' and with 'others'.